Analisis Penggunaan Bahasa dalam Film Ngeri-Ngeri Sedap - Mutia Alya Surianto; Diva Nayaka Siswadi; Alan Mustaqim Nst; Nur Indah Lestari; Tri Indah Prasasti (PT. Pustaka Cendekia Publisher, 2025)
This study analyzes the use of language in the Ngeri-Ngeri Sedap film with the aim of revealing the patterns of language use that occur in the film, especially in terms of language variation, code-switching, and code-mixing, and how social factors influence the use of language in communication between characters. The methods used in this study are the free listening technique and the note-taking technique. The free listening technique is used to observe the use of language in the film without direct interaction with the speaker, while the note-taking technique is used to document relevant findings in the dialogue and conversation between characters. The results of the study show that the Ngeri-Ngeri Sedap film uses a mixture of Indonesian, Batak, and a little Sundanese and Javanese. The use of this language functions as a communication strategy that reflects cultural identity and strengthens the emotional aspect in the interaction between characters. In addition, the code-switching and code-mixing that occur in the conversation between characters illustrate the social dynamics and the reality of communication in a multilingual society. Thus, the use of language in this film not only acts as a means of communication, but also as a medium to convey cultural messages and social values inherent in the lives of the Batak people..